ANALISIS PEMANFAATAN SUMBER BELAJAR OLEH GURU PPKn KELAS X - Nely Rohana; Okianna Okianna; Bambang Budi Utomo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research is a qualitative research. Data collection techniques in this research is to use observation techniques, interviews, and documentary studies. While the data collection tools used are interview guides, observation guides, log books and archives. The results showed that 1) Types of variations in the use of learning resources by PPKn teachers in Pontianak's Panca Bhakti High School were less varied. 2) Why teachers do not use varied learning resources in PPKn learning, based on the results of research conducted by researchers at Pontianak's Panca Bhakti High School, this is because learning resources used are only based on the needs of PPKn teachers, and because of time constraints in the use of learning resources. 3) In the selection of learning resources by the Panca Bhakti Pontianak High School PPKn teacher it was already good. This is seen from the teacher's attention to the accuracy of learning resources with subject matter and instructional goals, besides the teacher is very concerned about the ease of getting learning resources, and the teacher is very concerned about the suitability of learning resources with student abilities. Keyword : Utilization of Learning Resources, High School.